2018
DOI: 10.1103/physrevapplied.10.034005
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Photogalvanic Spin-Battery

Abstract: Pure spin-current is of central importance in spintronics. Here we propose a two-dimensional (2D) spinbattery system that delivers pure spin-current without an accompanying charge-current to the outside world at zero bias. The principle of the spin-battery roots in the photogalvanic effect (PGE), and the system has good operational stability against structural perturbation, photon energy and other materials detail. The device principle is numerically implemented in the 2D material phosphorene as an example, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 59 publications
(79 reference statements)
1
39
0
Order By: Relevance
“…[ 16–18 ] More recently, Xie et al reported a PGE spin battery device based on 2D phosphorene not only generating pure spin current but also collecting photons, which provides a novel direction in the development of spintronic devices. [ 10 ]…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…[ 16–18 ] More recently, Xie et al reported a PGE spin battery device based on 2D phosphorene not only generating pure spin current but also collecting photons, which provides a novel direction in the development of spintronic devices. [ 10 ]…”
Section: Figurementioning
confidence: 99%
“…[6] Recently, research has shown that light illumination is an effective way to produce current and modulate the valley current, charge, and spin in nanomaterials. [7][8][9][10][11][12] Furthermore, a detectable photocurrent can be generated by light irradiation with no need of external bias in the systems lacking space inversion symmetry, which is known as photogalvanic effect (PGE). [13] In recent years, the PGE has been extensively studied in low-dimension materials, such as monolayer silicene, [14] h-BN/Gr/h-BN vdW heterostructure, [15] S-doped monolayer black phosphorus, [9] and other nanoribbons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It should keep in mind that NEGF–SCF theory is not a ground state theory because it is determined by a nonvibrational and nonequilibrium density matrix. In this regard, more details can be found in the pioneering works by Guo et al…”
Section: Photoresponsivity and Photocurrentmentioning
confidence: 99%
“…The functionalization and application of BP inevitably involve with strains originating from the supporting substrates and contacts . Moreover, the strain engineering is also a significant mechanism to tailor and modulate the physical properties of 2D materials Therefore, it is important to identify the strain‐induced deformation patterns and clarify the relationship between strain and resulted variations of lattice bond parameters in BP.…”
Section: Introductionmentioning
confidence: 99%